Peran Guru Dalam Pembentukan Karakter Siswa - Faelasup; Baiq Uswatun Hasanah (Educompassion: Jurnal Integrasi Pendidikan Islam dan Global, 2025)
Islamic Religious Education (PAI) plays an important role in shaping the character of students. As the frontline in religious learning, PAI teachers have a great responsibility to guide and develop character values in their students. However, the facts on the ground show that there is a gap between the goals of PAI learning and its practice in shaping student character. This study aims to evaluate the role of PAI teachers in creating student character in schools. In addition, this research also seeks the factors that support and hinder the role of PAI teachers in creating student character. This research uses a qualitative case study, and data is collected through observation, documentation, and in-depth interviews. This research involved PAI teachers, school principals, and students. The results show that PAI teachers play an important role in shaping student character through exemplary behavior, habituation, and integration of religious values in learning. The supporting factors for the role of PAI teachers include the support of school principals, collaboration with parents, and a conducive school culture. Meanwhile, the inhibiting factors include the administrative burden of teachers, limited facilities and infrastructure, and lack of training for PAI teachers.